Influence of epidemiological factors on asthma phenotypes among asthma patients attending a tertiary care center – A cross-sectional study - Mededi, Satish Babu; Varghese, Jereen; Rajalingam, Ragulan; V, Viswambhar; Thomas, Nithin (Asian Journal of Medical Sciences, 2022)
Background: Asthma is a heterogeneous disease presenting with various phenotypes usually characterized by chronic airway inflammation. Aims and Objectives: The aim of the study was to identify epidemiology of bronchial asthma phenotypes in patients attending to tertiary care center. Materials and Methods: This was a descriptive cross-sectional study involving 69 patients who are suspected to have asthma according to the Global Initiative for Asthma guidelines. The data of each patient were collected on a proforma specially designed for this study on demographic data, socioeconomic status, body mass index, exposure to environmental factors, and other history-related questions. Sputum cytology and absolute eosinophil count were also examined using coGuide and P<0.05 was considered significant. Asthma phenotypes were the primary outcome and association of environmental factors with asthma phenotypes was the secondary outcome. Results: Out of 69, majority 26 (37.7%) were aged 31–40 years; 35 (50.7%) males and 34 (49.3%) were females. Fifty-eight (84.1%) were illiterate and 46 (66.7%) belonged to low class. Sputum cytology report showed that majority of them, 66.7%, had eosinophilia. The majority, 48 (69.6%), of the participants were triggered by weather and 55.1% had a history of respiratory tract infections. Thirty-three (47.83%) participants had obesity associate asthma, 34 (49.28%) had allergic asthma, and 20 (28.99%) had smoking-related asthma phenotypes. The difference in the proportion of few environment factor was significant for allergic and smoking-related asthma (P>0.005). Conclusion: The factors associated with the asthma phenotypes will help us further in anticipating the clinical course and better management of the specific phenotypes.